ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN ROKOK ELEKTRIK PADA SISWA SMA MUHAMMDIYAH1 KOTA PEKANBARU - Iril, CHAIRiL (Journal of Hospital Administration and Management (JHAM), 2025)
The increasing use of electronic cigarettes (vapes) among adolescents has become a significant public health concern, driven by the perception that vaping is safer than traditional smoking and by strong social and media influences. This study aimed to analyze the factors influencing electronic cigarette use among students of SMA Muhammadiyah 1 Pekanbaru, including perceived health risks, peer pressure, media exposure, and family role. A quantitative cross-sectional design was employed with a total sample of 113 students selected through simple random sampling. Data were collected using questionnaires and analyzed using the Chi-Square test and Cramer's V. The results indicated significant associations between vaping behavior and perceived health risks (p = 0.012; Cramer’s V = 0.25), peer pressure (p = 0.001; Cramer’s V = 0.36), media exposure (p = 0.004; Cramer’s V = 0.29), and family role (p = 0.018; Cramer’s V = 0.24). Peer pressure was identified as the strongest influencing factor. These findings suggest that adolescent vaping behavior results from interactions among individual perceptions, social dynamics, and media influence. Comprehensive prevention strategies should include health education, strengthened parental supervision, peer-based interventions, and digital literacy programs to reduce vape use among students. Keywords: electronic cigarettes, adolescents, health risk perception, peer influence, media exposure